THE ROLE OF INTERNET OF THINGS (IOT) IN TRANSFORMING ACCOUNTING INFORMATION SYSTEMS: A SYSTEMATIC LITERATURE REVIEW - Sovia Irawaty Sihombing; Sambas Ade Kesuma; Fahmi Natigor Nasution; Keulana Erwin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The rapid emergence of the Internet of Things (IoT) has transformed how accounting information systems (AIS) operate in the digital era. This study presents a Systematic Literature Review (SLR) of ten international journal articles published between 2023 and 2024 to analyze IoT’s influence on accounting practices, adoption models, and organizational performance. The findings reveal that IoT integration improves the timeliness, accuracy, and transparency of financial data while supporting automation and predictive analytics in accounting. When combined with other technologies such as Blockchain and XBRL, IoT enhances interoperability, auditability, and traceability across financial systems. The dominant theoretical frameworks include the Technology Acceptance Model (TAM), the Technology–Organization–Environment (TOE) model, and Socio-Technical Systems Theory, highlighting the interplay between technology and human factors. Despite these benefits, research gaps persist in empirical validation, long-term sustainability, and data governance. This review contributes to digital accounting scholarship by proposing an integrative view of IoT-based accounting and identifying future research opportunities to strengthen accountability, efficiency, and strategic decision-making in digitalized financial environments.